Genealogi Hukum Ekonomi Islam Bottom-Up: Dari Praktik Perdua dan Jual Janji ke Skema Pembiayaan BRK Syariah - Bobby Ferly; Asasriwarni Asasriwarni; Ikhwan Ikhwan; Salma Salma; Elfia Elfia (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
The discourse of Islamic economic law in Indonesia often highlights the tension between a textualist (top-down) approach and a sociological reality (bottom-up). This study traces the genealogy of Islamic economic law in Riau Province through a bottom-up approach, with a focus on the full conversion of PT Bank Riau Kepri (BRK) into an Islamic bank. This conversion was driven by regional policies and Malay-Islamic cultural identity based on the principle of "adat berandi syarak". This research fills the gap in the literature that tends to focus on formal compliance, by examining the socio-legal origins of Islamic banking products. Through qualitative methodology and three theoretical pillars—legal genealogy, the concept of living law, and the principle of 'urf in ushul fiqh—this study traces the evolution of local customary practices such as perdua (agricultural revenue sharing) and promiscuity (conditional buying and selling as an informal loan) into BRK Syariah formal financing products. The results of the analysis show that the value of partnership and risk sharing of the two is manifested in the muzara'ah and musharakah schemes, while the asset-based financing function of selling promises is refined into murabahah and musharakah mutanaqisah products. This study concludes that BRK Syariah products are the result of a contemporary synthesis between fiqh and living customary law, reflecting the privatization of Islamic economic law based on Riau Malay local wisdom.